2003
DOI: 10.5194/nhess-3-423-2003
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the 1991 Randa rockslides (Valais, Switzerland)

Abstract: Abstract. About 22 mio m 3 of rock fell from a cliff near the village of Randa (10 km north of Zermatt, Switzerland) on 18 April 1991. A second retrogressive rockslide of about 7 mio m 3 followed on 9 May 1991. At present, a rock mass situated above the scarp is still slowly moving toward the valley, involving several mio m 3 of rock.A kinematic approach to study of this well-documented rockslide was made "a posteriori" in order to identify the parameters relevant to the detection of such failures involving la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 2 publications
(2 reference statements)
0
69
0
Order By: Relevance
“…An orientation of 095/70 was used for the lateral release plane, while an orientation of 135/40 for the basal shear zone was found to best match the trace observed with GB-DInSAR. This orientation also matches the orientation of the basal failure surface of the second 1991 event (Sartori et al, 2003) and the azimuth of geodetic displacement vectors. For the back boundary to the north-west a nearly vertical plane as given by Willenberg et al (2008a) was assumed.…”
Section: Volume Calculationmentioning
confidence: 72%
See 2 more Smart Citations
“…An orientation of 095/70 was used for the lateral release plane, while an orientation of 135/40 for the basal shear zone was found to best match the trace observed with GB-DInSAR. This orientation also matches the orientation of the basal failure surface of the second 1991 event (Sartori et al, 2003) and the azimuth of geodetic displacement vectors. For the back boundary to the north-west a nearly vertical plane as given by Willenberg et al (2008a) was assumed.…”
Section: Volume Calculationmentioning
confidence: 72%
“…Possibly only a few discontinuities are active within lower parts of the instability, whereas most of the deformation is localized along the basal rupture plane. We interpret this displacement pattern as translational movement on a planar or stepped shear surface, as hypothesized by Willenberg et al (2008b), Jaboyedoff et al (2004), and Sartori et al (2003). The transition between toppling and translational failure occurs at a sharp change of the slope angle in the 1991 failure scarp from about 80 • at the top to about 60 • below.…”
Section: Implications For Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…On 18 April 1991, 22 million m 3 of rock fell from the steepest cliff of the Matter valley near the village of Randa (10 km north of Zermatt, Switzerland) (Schindler et al, 1993;Sartori et al, 2003). On 9 May 1991 a retrogressive rockslide of about 7 million m 3 fell down from the upper part of the 18 April scar (Fig.…”
Section: Geological and Geomorphological Settingsmentioning
confidence: 99%
“…Although poorly documented, water is often mentioned as a triggering mechanism for failure of rocks with well-developed pre-existing fractures networks, and thus the cause for rock slides [1]. Sartori et al [2] observed that "explosion-like failure of rock slabs and sprays of water under pressure" characterized the events preceding the 1991 Randa rockslide (22 × 10 6 m 3 ) in Switzerland. Similar observations have been made in other cases in which events have been triggered close to and above the main spring draining the aquifer contained in a slope.…”
Section: Introductionmentioning
confidence: 99%